Facile prepared tropinone-based enone dyes with visible-light induced photothermal liquefaction and cold crystallization properties for reusable and switchable adhesive. (May 2022) - Xue, Tanlong; Yuan, Hengda; Sun, Jingxian; Lu, Guoqiang; Si, Zhihao; Huang, Boyuan; Tang, Ruifen; Nie, Jun; Zhu, Xiaoqun
Abstract: The solid-liquid phase transition of adhesives triggered by two different wavelength light stimuli enables the switchable and reusable character. The adhesive which could be liquified by photothermal effect by single-wavelength light stimulus and solidified by natural cooling is much easier to operate but little developed. In this work, a class of tropinone-based enone dyes (TPs), prepared by one-pot Claisen-Schmidt condensation, were explored as a novel kind of single-wavelength light-switchable adhesives. TPs could absorption visible light and are non-fluorescent. By changing the length of alkoxy groups, the melting point and crystallization behavior were regulated. Especially, TP6 and TP8 could form overcooled liquid during the cooling process, thus enabling a proper adhesion operation window. Under 405 nm LED irradiation, the rapid solid-liquid transformation was achieved for some of TPs due to the high thermal conversion ability. TPs presented good adhesion strength toward glass plates. Among them, TP8 could work as a reusable and light-switchable adhesive. Graphical abstract: TP8 is a reusable and switchable adhesive. Image 1 Highlights: A series of tropinone-base enone dyes (TPs) with different melting points and crystallization behaviors were synthesized. The photophysical properties of TPs were investigated. Some of TPs showed photothermal liquefaction under 405 nm LED light (800 mW/cm 2 ). TPs were studied as adhesive toward glass substrate. TP8 is a reusable and switchable adhesive.